Ethics of the Physician's Role in Health-Care Cost Control: AOA Critical Issues. (20th July 2016) - Bosco, Joseph; Iorio, Richard; Barber, Thomas; Barron, Chloe; Caplan, Arthur
Abstract : Abstract: The United States health-care expenditure is rising precipitously. The Congressional Budget Office has estimated that, in 2025, at our current rate of increased spending, 25% of the gross domestic product will be allocated to health care. Our per-capita spending on health care also far exceeds that of any other industrialized country. Health-care costs must be addressed if our country is to remain competitive in the global marketplace and to maintain its financial solvency. If unchecked, the uncontrolled rise in health-care expenditures will not only affect our capacity to provide our patients with high-quality care but also threaten the ability of our nation to compete economically on the global stage. This is not hyperbole but fiscal reality. As physicians, we are becoming increasingly familiar with the economics impacting health-care policy. Thus, we are in a unique position to control the cost of health care. This includes an increased reliance on creating and adhering to evidence-based guidelines. We can do this and still continue to respect the primacy of patient welfare and the right of patients to act in their own self-interest. However, as evidenced by the use of high-volume centers of excellence, each strategy adapted to control costs must be vetted and must be monitored for its unintended ethical consequences. The solution to this complex problem must involve the input of all of the health-care stakeholders, including the patients, payers, and providers. Physicians ought to play a role in designing and executing a remedy. After all, we are the ones who best understand medicine and whose moral obligation is to the welfare of our patients.